COMPOSITION AND IMMUNODOMINANT SITES OF THE CARBOHYDRATE ANTIGEN OF CLOSTRIDIUM BOTULINUM TYPE E SAROMA - TAKEOKA, AYA; NAGAO, SHIGKI; TAKUMI, KENJI (Journal of general and applied microbiology, 1991)
Carbohydrae complex antigen, which was common among the nonproteolytic Clostridium botulinium, was purified from the hot-formamide extract of the cell wall by means of a sequence of ionexchange and gel filtration chromatography. The antigen consisted of glucose, glucosamine, galactosamine, D-alanine, and phosphorus with a molar ratio of 1.5:1.5:0.25:0.25:1:1. Neither ribitiol nor glycerol appeared. In quantitative precipitin inhibition tests, α-methyl glucoside and β-methyl glucoside gave 85% and 70% inhibition respectively at an equivalence point of the antigen-antibody reaction. D-Alanine or glucosamine did not inhibit the reaction. Partial acid hydrolysis of the antigen, by which about a half of the glucose moiety was eliminated, resulted in a complete loss of the antigenic activity.